A neglected manuscript: A Danish version of Amadís de Gaula - Richter, Anna; Glauser, Jürg (Danske Studier, 2018)
»In the long history of European prose fiction few works are to be found that have exercised more influence not only on literature proper but also on manners and customs, or that have enjoyed a more enduring popularity, than the romance of chivalry entitled Amadís de Gaula.« It has been a common place in (Scandinavian) literary historiography that the chivalric romance Amadís de Gaula was well-known and read also in Northern Europe, but never had been translated into any Scandinavian language. After giving a very short survey of the European diffusion of the Amadís novel, this contribution reports on a manuscript that indeed contains a Danish translation of this chivalric romance, held at The Royal Library in Copenhagen.